2014
DOI: 10.1021/ie502599p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chitosan-Grafted BPPO Ultrafiltration Composite Membranes with Enhanced Antifouling and Antibacterial Properties

Abstract: In this study, chitosan was successfully grafted onto the top surface of a bromomethylated poly(phenylene oxide) (BPPO) ultrafiltration membrane without pretreating the membrane at harsh conditions and/or using other cross-linkers. Due to the grafting of polar groups of chitosan onto the membrane top surface, the hydrophilicity of the membrane top surface and the polar component of the total surface energy are improved compared to the pristine BPPO membrane. Theoretical calculation shows that the polar compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The filtration test was carried out in HP4750 cell (Sterlitech, Kent, WA, USA) with compressed nitrogen gas to control the feed pressure. [ 37 ] To fix the fibre membrane, the non-porous stainless steel supporting disc with a circular hole in the centre was used. The disc has a diameter of 50 mm and a thickness of 2 mm meanwhile the hole in its centre has a diameter of 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The filtration test was carried out in HP4750 cell (Sterlitech, Kent, WA, USA) with compressed nitrogen gas to control the feed pressure. [ 37 ] To fix the fibre membrane, the non-porous stainless steel supporting disc with a circular hole in the centre was used. The disc has a diameter of 50 mm and a thickness of 2 mm meanwhile the hole in its centre has a diameter of 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Feng et al 37 modied the surface of BPPO UF membranes using chitosan as graing agent. The modied BPPO membrane showed a slight decrease in water permeation aer 6 h graing duration.…”
Section: -20mentioning
confidence: 99%
“…More recently, the research efforts have been devoted to the development of antimicrobial fouling membranes. For example, modification of the physicochemical properties of membrane surfaces, such as surface charge and hydrophilicity, could effectively minimize the bacteria attachment. However, it has been shown that the membrane is prone to loss of the microbial resistance even upon a slight surface alteration. For example, once the first layer of microorganisms is deposited, their exponential growth is expectable, and this could be developed into severely membrane performance loss .…”
Section: Introductionmentioning
confidence: 99%